Producing cognitive discourse functions in disciplinary Basque writing: developmental patterns across secondary education and L1 profiles - Arias-Hermoso, Roberto; Garro Larrañaga, Eneritz; Imaz Agirre, Ainara; Dalton-Puffer, Christiane (International journal of bilingual education and bilingualism, 2025)
The present study explores the developmental patterns of bilingual secondary education students in a disciplinary writing task in Basque, their language of instruction. A cross-sectional sample of 547 bilingual students (Years 7-10) enrolled in Basque Model D immersion programmes completed a source-based writing task requiring them to produce two cognitive discourse functions: argue and compare. Students reported to have either Basque, Spanish or both as their L1. The corpus was analysed with an analytical rubric that considered students' performance in three dimensions: arguing, comparing and using sources. Linear mixed models were used to assess the effect of Year and L1 on the three dimensions. Findings showed positive developmental patterns from Y7 to Y10 in all measures for all L1 profiles, with varying turning points. Most measures reached statistical significance when comparing two-year cycles. Similar developmental patterns were found in learners' writing, especially between Y7 and Y9, after which Basque L1 students improved and Spanish L1 students stagnated. Students having both as their L1 showed the most irregular patterns. In conclusion, results show developmental patterns in disciplinary cognitive discourse function production and source-based writing. Implications for the development of disciplinary literacies and bi/multilingual education are discussed.